2021
DOI: 10.1038/s41467-021-27577-x
|View full text |Cite
|
Sign up to set email alerts
|

A machine and human reader study on AI diagnosis model safety under attacks of adversarial images

Abstract: While active efforts are advancing medical artificial intelligence (AI) model development and clinical translation, safety issues of the AI models emerge, but little research has been done. We perform a study to investigate the behaviors of an AI diagnosis model under adversarial images generated by Generative Adversarial Network (GAN) models and to evaluate the effects on human experts when visually identifying potential adversarial images. Our GAN model makes intentional modifications to the diagnosis-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…If the diagnostic performance is improved, a new model can be adopted so that the diagnostic performance of the CLS can be guaranteed to be stable or improve but not decrease. A study by Zhou et al 37 suggests an imperative need for research on medical AI model safety issues; thus, the use of optimal methods in this study ensured the safe operation of the model.…”
Section: Discussionmentioning
confidence: 92%
“…If the diagnostic performance is improved, a new model can be adopted so that the diagnostic performance of the CLS can be guaranteed to be stable or improve but not decrease. A study by Zhou et al 37 suggests an imperative need for research on medical AI model safety issues; thus, the use of optimal methods in this study ensured the safe operation of the model.…”
Section: Discussionmentioning
confidence: 92%
“…Zhou, et al, [19] conducted an interesting study on the effect of adversarial images within the domain of breast cancer mammography. They found that human radiologists could identify the adversarial images at a generally higher rate of success than a deep learning-based computer-aided diagnosis system, illustrating the need for ongoing work in this area.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited awareness by the public and stakeholders about the level of evidence required to validate safety, security (39) and each specific clinical claim by AI software solutions, as well as the evidential requirements to verify the added-value for appropriate reimbursement.…”
Section: Regulatory and Legal Aspectsmentioning
confidence: 99%